2015
DOI: 10.1186/s12889-015-1550-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between diet, physical activity and body fat distribution: a cross sectional study in an Indian population

Abstract: BackgroundObesity is a growing health problem in India and worldwide, due to changes in lifestyle. This study aimed to explore the independent associations between dietary and physical activity exposure variables and total body fat and distribution in an Indian setting.MethodsIndividuals who had participated in the Indian Migration Study (IMS) or the Andhra Pradesh Children And Parents' Study (APCAPS), were invited to participate in the Hyderabad DXA Study. Total and abdominal body fat of study participants wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
31
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 53 publications
9
31
0
7
Order By: Relevance
“…Weight gain is usually due to excessive consumption of calories along with lifestyle habits and low physical activity. Along with the daily caloric intake, the composition of the diet may also be an important factor in understanding obesity and its prevention (2) . The result in Table 4 shows a positive significant relationship of fat percentage and visceral fat with energy and carbohydrate consumption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weight gain is usually due to excessive consumption of calories along with lifestyle habits and low physical activity. Along with the daily caloric intake, the composition of the diet may also be an important factor in understanding obesity and its prevention (2) . The result in Table 4 shows a positive significant relationship of fat percentage and visceral fat with energy and carbohydrate consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Weight is a combination of lean mass, fat mass, water, visceral fat etc and an understanding of which factors favour fat mass deposition could help in management of obesity in a scientific manner (2) . The results from this study provide scope to various researchers to study in-depth the various other factors impacting body composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu, et al (2010) stated that in the adult population in China for 30-79 years old showed that the western diet increased the risk of overall obesity and central obesity (7). The populations in India, physical activity, high-fat diet, and protein increased a fat in the body (9). Wiardani (2016), stated that in adult tour guides as well as showed the subjects proportion who consumed macronutrients above the recommended adequacy was more than the recommended consumption (10).…”
Section: Introductionmentioning
confidence: 99%
“…Wrong food consumption behavior and physical inactivity cause the body's metabolism impaired that can cause overweight and obesity. Bowen (2015) showed that there is a relationship between the intake of energy, protein, and fat with central fatness. Further Vera & Naomi (2012) indicates that there is a relationship between the consumption of carbohydrates and fiber with the incidence of central obesity.…”
Section: Introductionmentioning
confidence: 99%